Asia-Pacific Survey of Physicians on Asthma and Allergic Rhinitis (ASPAIR): physician beliefs and practices about diagnosis, assessment, and treatment of coexistent disease - Aggarwal, Bhumika (J Asthma Allergy, 2018)
BACKGROUND: Asthma and allergic rhinitis (AR) frequently coexist, and having both asthma and AR is associated with uncontrolled asthma and a heavier disease burden. The Asia-Pacific Survey of Physicians on Asthma and Allergic Rhinitis (ASPAIR) aimed to assess physicians’ perceptions and their management practices for patients with coexistent disease. MATERIALS AND METHODS: A total of 1,204 general physicians and pediatricians from six countries in Asia, who routinely treat asthma patients, were interviewed in-person. Physicians were questioned about their attitudes and beliefs of coexistent asthma-AR, how they diagnose and treat patients, and their knowledge of international guideline recommendations. RESULTS: Physicians reported that 45% of their patients with asthma have coexistent AR and 37% of their patients with AR have coexistent asthma. Most physicians (77%) agreed that coexistent asthma-AR is a genuine condition and that patients suffer worse symptoms with both the conditions vs one alone (86%). Although nearly all agreed that both asthma and AR should be treated (91%) and that intranasal (INS) and inhaled corticosteroids (ICS) could be given concurrently to these patients, 40% also thought that treating both conditions effectively at the same time is difficult, and approximately a quarter believed that corticosteroid therapy should be delayed in children for both asthma and AR. While there was universal recognition and acceptance that guidelines provide sufficient information for treating uncontrolled coexistent disease (≥80% physicians in all countries), physicians revealed that 41% of their asthma patients are treated with short-acting rescue medications alone, and only 47% responded that treatment with concurrent INS and ICS, as recommended in the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines, was their preferred treatment for coexistent disease. CONCLUSION: The ASPAIR survey demonstrates a widespread acceptance of coexistent asthma-AR, and the associated burden, but highlights the need for increased healthcare practitioner communication and awareness to improve appropriate treatment and management of these coexistent conditions.